Cytogenetic and molecular characterization of an SRY-negative 46, XX ovotesticular DSD: a case report - Moura Carvalho, Natalia Dayane; Carvalho Passos, Tirciana; Mesquita Gadelha Prazeres, Vania; Fantin, Cleiton (Revista de Ciências Médicas e Biológicas, 2021)
Introduction: Ovotesticular disorder of sex development is a rare condition by the concomitant presence of testicular and ovarian tissue, and usually presents genital ambiguity. Are chromosomally heterogeneous, and cytogenetic analyses is relevant. Objective: report on a patient from Manaus, Amazonas state with ovotesticular disorder of sex differentiation 46, XX and SRY-negative. Case report: Patient of 19 years, first child of non-consanguineous parents. At birth, the patient was diagnosed with genital ambiguity and, without early diagnosis, he was registered as being of the male sex. The patient underwent surgery to correct bilateral cryptorchidism, orchiopexy and colpectomy. During puberty, he developed female and male sexual characteristics. Endocrinological (normal total testosterone and estradiol as high follicle-stimulating hormone and luteinizing hormone), histopathological (right gonad, ovarian follicles and left gonads, atrophic testicles), karyotype (46, XX) and molecular (SRY-negative). Diagnosis of ovotesticular disorder of sex development was established. The patient chose to remain male and underwent bilateral mastectomy, vaginal colpectomy and bilateral gonadectomy. Currently, the patient receives hormonal replacement therapy, follow-up with a multi-professional approach and awaits masculinizing genitoplasty. Discussion: In diagnostic research, cytogenetic and molecular analysis are primary tools. For OT-DSD individuals with 46, XX, the female sex is suggested as the best sex option. Unlike the reported cases, the patient chose the male sex, since the sex at registration of birth was important in his choice. Conclusion: Cytogenetic and molecular analyses allowed us to assist in the etiological diagnosis of the patient with OT-DSD from Manaus. However, molecular analyses are necessary to elucidate the genes involved in the sexual determination of this patient.